(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
In 2017 a new research team was established by pediatric neurologists, psychologists, teachers, researchers and preschool experts at the University of Sopron Benedek Elek Faculty of Pedagogy. The research field is concentrated on a recently new topic defined ’early childhood neuropedagogy’. The main focus of the collaboration is revealing of use of EMOTIV EPOC+ EEG devices in the practice of early childhood education. The project is financed by the Ministry of Human Capacities (Nr. 32388-2/2017 INTFIN). In our present research first we overviewed the classical ways of monitoring chlidren’s development (e.g. different test and surveys) then we analysed the possibilities of using EMOTIV EPOC+ EEG devices in the field of educational sciences. We focused on an innovative-reflective approach, concentrated on the following success criteria of innovation in the pedagogical practice: e.g. relative advantage, compatibility, the needs and sensibility of potential adopters, complexity, observability, trialability and technical challenges (Rogers, 2002; Kissné, 2015).